(untitled) (Филолошки студии, 2019)
The aim of this article is to investigate the main ideas of David Hume’s philosophical and aesthetical approaches and to stress that the significance of his interpretations of beauty and taste today are even more important then hundred years ago. This year (2011), celebrating 300 years from the birth of the philosopher (1711) it’s very important, once again, to point out that Hume’s essay “Of the Standard of Taste” today is a canonical text connected with the category of taste, and according to the opinions of the most important contemporary aestheticians (Beardsley, Shelley, Dickie), along with Kant’s third Critic, it is foundation work of the modern aesthetical theory.